Being at Leisure in blue spaces: The role of Leisure in amplifying the well-being benefits of the seaside. Issue 2 (22nd November 2022) - Jarratt, David; Gammon, Sean; Davies, Nick; Ward, Jason
This article utilises work from Leisure Studies and various elements of Psychology (Leisure and Ecological Psychology in particular) to frame an empirical exploration of the leisure health receptor theory. We question if being in a leisure state of mind magnifies the feelings of well-being experienced in blue spaces (aquatic environments), namely, the promenade areas of seaside resorts in North-West England. We surveyed two groups in these places, those in a leisure state of mind and those who were not, asking how they viewed these blue spaces and how they made them feel – within the context of leisure and well-being. We devised a Seaside Well-being Index, which summarised well-being-related positive feelings about these leisure and work experiences at the coast. The key finding was that being in a leisure state of mind accentuates feelings of well-being associated with exposure to blue spaces. We also consider the role of savouring and affordance in this process. The potential impact of this research is to encourage a scholarly conversation on the role that leisure mind-states can play in improving well-being outcomes associated with blue spaces – not just in theory but in well-being-related interventions by practitioners.